Correlation of TIMI Risk Score and GRACE Risk Score with Lesion of Coronary Artery Disease in Patients with Non-ST Segment Elevation Acute Coronary Syndrome - Maroof Hassan, Ghulam Kubra, Mehwish Sabeen, Deebaj Nadeem, Asma Murtaza, Faiza Sikandari (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the correlation of “thrombolysis in myocardial infarction (TIMI)” and “Global Registry of Acute Coronary Events (GRACE)” risk score with lesion of coronary artery disease in patients with non-ST segment elevation acute coronary syndrome. Study Design: Cross-sectional study. Place and Duration: The Department of adult cardiology, “National Institute of Cardiovascular Diseases (NICVD)”, Karachi, Pakistan, from January 2021 to July 2021. Methodology: Demographics, weight, height, risk factors along with the required information needed for TIMI and GRACE score were obtained at the time of presentation in emergency department as per the scoring criteria. SYNTAX score was calculated after performing conventional angiography of the patients, using SYNTAX.com calculator. Results: In a total of 104 patients, the mean age was 57.21±12.22 years while 56 (53.8%) patients were male. Hypercholesterolemia was found in 33 (31.7%) patients. Mean score of TIMI was calculated as 4.680±2.064 while SYNTAX score was calculated as 26.45±12.94 and the correlation between TIMI risk score and SYNTAX score was noted as (r=0.109) and P value was found to be non-significant i.e. (P=0.270). Mean score of GRACE was noted as 135.38±90.88 while SYNTAX score was noted as 26.45±12.94 and the correlation between GRACE risk score and SYNTAX score was documented as (r=0.179) and P value was found to be non-significant i.e. (P=0.068). Practical Implications: Both TIMI and GRACE risk scoring systems showed weak correlations with SYNTAX scores. Conclusion: There is a weak correlation between TIMI risk score and SYNTAX score as well as GRACE risk score and SYNTAX score. Keywords: Acute coronary syndrome, coronary artery disease, GRACE score, myocardial infarction, thrombolysis.